2021
DOI: 10.1111/ocr.12513
|View full text |Cite
|
Sign up to set email alerts
|

Automated landmarking for palatal shape analysis using geometric deep learning

Abstract: Objectives: To develop and evaluate a geometric deep-learning network to automatically place seven palatal landmarks on digitized maxillary dental casts. Settings and Sample Population:The sample comprised individuals with permanent dentition of various ethnicities. The network was trained from manual landmark annotations on 732 dental casts and evaluated on 104 dental casts. Materials and Methods:A geometric deep-learning network was developed to hierarchically learn features from point-clouds representing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…AI models developed for application in orthodontics have mainly focused on: the automated identification of cephalometric landmarks [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]; the estimation of bone age and maturity using cervical vertebra and hand-wrist radiographs [32][33][34][35][36][37][38][39][40][41][42][43]; palatal shape analysis [44,45]; determining the need for orthodontic tooth extractions [46][47][48][49][50][51][52]; automated skeletal classification [53,54]; and the diagnosis and planning of orthognathic surgeries [55][56][57][58][59][60][61]…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…AI models developed for application in orthodontics have mainly focused on: the automated identification of cephalometric landmarks [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]; the estimation of bone age and maturity using cervical vertebra and hand-wrist radiographs [32][33][34][35][36][37][38][39][40][41][42][43]; palatal shape analysis [44,45]; determining the need for orthodontic tooth extractions [46][47][48][49][50][51][52]; automated skeletal classification [53,54]; and the diagnosis and planning of orthognathic surgeries [55][56][57][58][59][60][61]…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The recent technological advancements have resulted in the development of AI based models designed for palatal shape analysis. Croquet B et al [44] reported on a deep learning model designed for analyzing the palatal shape. This automatic model demonstrated excellent repeatability with promising accuracy.…”
Section: Ai Models Designed For Palatal Shape Analysismentioning
confidence: 99%
“…Automatized 3D cephalometric landmark annotation [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58]…”
unclassified
“…Although essential for the success of AI‐based diagnosis, the objective extraction of these morphological features is not easy. Nauwelaers et al developed a novel AI‐based method for the analysis of palatal 3D shape 26 and Croquet et al developed methods of automatic landmarking for analysis of the palatal shape 27 …”
mentioning
confidence: 99%